Social isolation in adults with cancer: An evolutionary concept analysis - Liang, Yanjing; Hao, Guihua; Wu, Mei; Hou, Lili (Frontiers in Psychology, 2022)
Background In extant literature, the concept of social isolation has been explored primarily in the context of older adults. However, people with cancer may also experience social isolation, and there is a need for increased clarity regarding this phenomenon in this population. Objective To conceptualize social isolation in adult cancer care. Methods PubMed, Web of Science, PsycINFO, CINAHL, China National Knowledge Infrastructure, Wanfang Data, and the Chinese Biomedical Literature Database were systematically searched using the key terms “cancer,” “social isolation,” “social alienation,” and “social exclusion” for studies (from the earliest date available to June 2022). The main disciplines involved were psychology, nursing, medicine, and public health. Rodgers’ evolutionary concept analysis was employed to clarify the antecedents, attributes, and consequences of social isolation in adults with cancer. Results A total of 60 eligible articles were reviewed entirely and the main findings were categorized into antecedents, attributes, and consequences. The antecedents of social isolation were classified into six categories: cancer-related physiological changes, cognitive beliefs, psychological wellbeing, unsatisfactory social supports or relationships, restrictions associated with receiving treatments, and social-level barriers. Attributes were characterized according to behavior or social avoidance and negative affective experiences, while consequences were attributed to low therapeutic compliance, poor health conditions and mental health problems, and low quality of life. White’s heuristic model is a potential theoretical context applicable to social isolation in adults with cancer. Conclusion This concept analysis provides a basis for developing multidimensional assessment tools and measures to alleviate social isolation in adults with cancer, a complex and varied phenomenon. However, while this review contributes to the current knowledge on social isolation in people with cancer, studies should further investigate the relationships among attributes associated with social isolation.